Pengembangan Bahan Ajar Interaktif Mahārah Istima’ Berbasis Keterampilan Abad-21 di MI Plus Al-Fatimah Bojonegoro - Ummi Inayati (eL Bidayah: Journal of Islamic Elementary Education, 2023)
The aims research is to describe the Development, Validity and Effectiveness of Interactive Teaching Materials in Mahārah Istima' based on 21st Century skill at Al-Fatimah plus Islamic Elementary School Bojonegoro. This study used the Research and Development (R&D) method there is using the ADDIE model. The results of this research and development are (1) the development of Interactive Teaching Materials in Mahārah Istima' based on 21st Century measuring 18x25cm and using Fusha Arabic. This teaching material consists of 8 chapters which contain major themes based on the 2013 curriculum. Each chapter is equipped with a barcode containing reading, vocabularies, conversation, practice, and songs which can be scanned with a smartphone. There are also practice questions at the end of semester I and semester II. (2) Based on the results of the validation test of the material expert lecturer, it shows that in terms of presentation of the material, a score of 86 is obtained in the valid category. Meanwhile, the results of the validation test for design expert lecturers obtained a score of 91 in the very valid category. The results of the Arabic teacher validation test obtained a score of 89 with a very valid category. This teaching material is also effective because the results of the paired sample t-test show a significant number between pre-test and post-test values with a significant value (2-tailed) p = 0.000, <0.05 [Tujuan penelitian ini adalah untuk mendeskripsikan Pengembangan, Kelayakan dan Efektivitas Bahan Ajar Interaktif Mahārah Istima’ Berbasis Keterampilan Abad-21 di MI Plus Al-Fatimah Bojonegoro. Penelitian ini menggunakan metode Research and Development (R&D) menggunakan model ADDIE. Adapun hasil penelitian dan pengembangan ini yaitu (1) bahan ajar interaktif maharah istima’ berbasis keterampilan abad-21 yang dikembangkan ini berukuran 18x25cm dan menggunakan Bahasa Arab Fusha. Bahan ajar ini terdiri dari 8 bab yang isinya berisi tema-tema besar berdasarkan kurikulum 2013. Pada masing-masing bab dilengkapi dengan barcode yang berisi qiroah, mufrodat, hiwar, tamrin, dan ghina’ yang bisa dipindai dengan smartphone. Terdapat juga soal latihan pada akhir semester I dan semester II. (2) berdasarkan hasil uji validasi dosen ahli materi menunjukkan bahwa dari segi penyajian materi memperoleh skor 86 dengan katagori valid. Sementara hasil uji validasi dosen ahli desain memperoleh skor 91 dengan katagori sangat valid. Adapun hasil uji validasi guru Bahasa arab memperoleh skor 89 dengan katagori sangat valid. Bahan ajar ini juga efektif karena hasil uji paired sample t-test menunjukkan angka yang signifikan antara nilai pre-test dengan post-test dengan nilai significant (2-tailed) p= 0.000, <0.05]